Oracle Designer handbook : a comprehensive system development method using Oracle's design tools - Koletzke, Peter; Dorsey, Paul (Berkeley, California : Osborne McGraw-Hill, 1999)
This authoritative guide provides a solid understanding of how to design and build a project that fully realizes the time-saving potential of Oracle Designer/2000. It takes the developer through each step of Oracle's CASE approach, revealing methodical steps and phases of producing software and practical ways that the Designer/2000 tool can support them.
Part I: Getting Started -- Part II: Life Cycle Phases -- Part III: Additional CADM Activities -- Part IV: Additional oracle designer activities.
Includes index.
Keywords: SOFTWARE ENGINEERING